Milano 2: the conceptualization of the ‘re-definition’ of urban life - Monza, Lidia (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
Since the 1960s, the majority of Western cities have been discussing sustainable urban development in order to respond to increasing poverty, crime, and unforeseen patterns within our urban environments. Social and economic inequality plus security issues are central themes in this public debate. Moreover, principles of neoliberalism have led to the constant privatization and economization of social life resulting in private entities in urban contexts playing a pivotal role in the last few decades. This has brought about new and extreme forms of urbanism and developed a new narrative in the urban political discourse. Through the example of Milano 2 (Italy), this paper investigates how an elitist project can establish an alternative conceptualization of ‘the urban’ and considers its implications on ‘the political’ and general urban development. Milano 2 operates on the pretense of giving its residents a ‘better place to live’ which involves a ‘re-definition’ of lifestyle and management organization through governance strategies. In order to assert that Milano 2 represents a ‘redefinition of urban life’, this paper builds up an argument starting from the analysis of public discourse about lifestyle. Furthermore, the paper considers management organization and its governance technologies from a conceptual point of view. By starting to study the sustainable urban development question from the elitist perspective, this paper adds to the discussion by regarding the normalization and acceptance of these urban experiments and it considers how master-planned communities work within the re-definition of lifestyles and management.